Cloning of a locus involved in Streptococcus mutans intracellular polysaccharide accumulation and virulence testing of an intracellular polysaccharide-deficient mutant. - Harris, G S (1992)
The streptococcal transposon Tn916 (Tcr) was used to isolate mutants of Streptococcus mutans altered in glycogen accumulation to investigate whether glycogenlike intracellular polysaccharides (IPS) play an important role in S. mutans-induced caries formation. S. mutans UA130 (serotype c) was transformed with the Escherichia coli plasmid pAM620 (Tn916), and the resultant transposon libraries were screened for glycogen content by iodine staining. A transposon mutant, designated SMS201, demonstrated a glycogen-deficient phenotype on glucose-enriched medium. Quantitative electron microscopy confirmed that IPS concentrations were significantly reduced in SMS201 relative to the wild-type progenitor strain, UA130. Importantly, reversion to wild type correlated at all times with loss of the transposon. Transposon excisants were used to facilitate cloning of the streptococcal gene(s) involved in glycogen biosynthesis and storage. A 2.1-kb chromosomal determinant (glgR) which encodes a putative regulator of S. mutans glycogen accumulation was isolated. A stable deletion mutation (delta glgR) was subsequently generated in E. coli and introduced into S. mutans by allelic exchange. The resultant glycogen synthesis-deficient mutant, SMS203, demonstrated a significantly reduced cariogenic potential (P less than 0.01) on the buccal, sulcal, and proximal surfaces of teeth in germfree rats, relative to animals challenged with the glycogen synthesis-proficient progenitor strain, UA130. These observations confirm previous reports (J. M. Tanzer, M. L. Freedman, F. N. Woodiel, R. L. Eifert, and L. A. Rinehimer, p. 597-616, in H. M. Stiles, W. J. Loesche, and T. L. O'Brien, ed., Proceedings in Microbiology. Aspects of Dental Caries. Special Supplement to Microbiology Abstracts, vol. 3, 1976) which implicate IPS as significant contributors to the S. mutans cariogenic process.